EKLF/KLF1-regulated cell cycle exit is essential for erythroblast enucleation - Gnanapragasam, Merlin Nithya (Blood, 2016)
The mechanisms regulating the sequential steps of terminal erythroid differentiation remain largely undefined, yet are relevant to human anemias that are characterized by ineffective red cell production. Erythroid Krüppel-like Factor (EKLF/KLF1) is a master transcriptional regulator of erythropoiesis that is mutated in a subset of these anemias. Although EKLF’s function during early erythropoiesis is well studied, its role during terminal differentiation has been difficult to functionally investigate due to the impaired expression of relevant cell surface markers in Eklf(−/−) erythroid cells. We have circumvented this problem by an innovative use of imaging flow cytometry to investigate the role of EKLF in vivo and have performed functional studies using an ex vivo culture system that enriches for terminally differentiating cells. We precisely define a previously undescribed block during late terminal differentiation at the orthochromatic erythroblast stage for Eklf(−/−) cells that proceed beyond the initial stall at the progenitor stage. These cells efficiently decrease cell size, condense their nucleus, and undergo nuclear polarization; however, they display a near absence of enucleation. These late-stage Eklf(−/−) cells continue to cycle due to low-level expression of p18 and p27, a new direct target of EKLF. Surprisingly, both cell cycle and enucleation deficits are rescued by epistatic reintroduction of either of these 2 EKLF target cell cycle inhibitors. We conclude that the cell cycle as regulated by EKLF during late stages of differentiation is inherently critical for enucleation of erythroid precursors, thereby demonstrating a direct functional relationship between cell cycle exit and nuclear expulsion.